Methods of Selecting a Compressor Station and Compressed Air Purification Systems - Askarov, R.V.; Ramazanov, E.B.; Askarova, N.Z. (Herald of Azerbaijan Engineering Academy, 2022)
The article offers a detailed breakdown of the process of selecting a compressed air station according to the needs of production, specifics of the environment, as well as the level of air purity and dryness requirements. Formulas for calculating the compressor power required by the consumer are given. The importance of taking into account pressure losses in the pneumatic network and the correct choice of the type of dryer and compressed air receiver is indicated, as it lowers the stress upon the compressor station and reduces the energy usage by up to 25%. Correspondence tables for the degree of air purification from contaminants in accordance with (ISO 8573-1:2010) directive are shown in this article. Recommendations on choosing the length and diameter of pneumatic lines in order to reduce pressure loss in the compressed-air network are given.diameter of pneumatic lines in order to reduce pressure loss in the compressed-air network are given.